2020
DOI: 10.1002/npr2.12121
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of heart rate variability indices in assessing the risk of an unsuccessful return to work after sick leave in depressed patients

Abstract: Aim The present study aimed to examine whether heart rate variability (HRV) indices in depressed patients measured at return to work after sick leave are related to the outcome of reinstatement. Methods This study included 30 workers who took a leave of absence due to major depressive disorder. HRV was measured twice, once when participants left work and another when they returned to work. One month after returning to work, 19 participants continued their original work (successful return group), while 11 faile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 26 publications
(51 reference statements)
2
14
0
Order By: Relevance
“…Moreover, the evidence that HRV might embody a vulnerability factor for the development of psychopathology raises the issue of whether in addition to be a trait-dependent feature, it may also be a state-dependent feature, associated with situational demands. Indeed, a series of studies have demonstrated that, not only baseline, but even task-related HRV could represent an index of clinical outcome in individuals with depression (Shinba et al, 2014; Shinba et al, 2020). Although resting-state HRV is a well-validated and feasible tool for the clinical practice, state-dependent HRV-fluctuations may increase the accuracy of HRV as a candidate endophenotype of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the evidence that HRV might embody a vulnerability factor for the development of psychopathology raises the issue of whether in addition to be a trait-dependent feature, it may also be a state-dependent feature, associated with situational demands. Indeed, a series of studies have demonstrated that, not only baseline, but even task-related HRV could represent an index of clinical outcome in individuals with depression (Shinba et al, 2014; Shinba et al, 2020). Although resting-state HRV is a well-validated and feasible tool for the clinical practice, state-dependent HRV-fluctuations may increase the accuracy of HRV as a candidate endophenotype of depression.…”
Section: Discussionmentioning
confidence: 99%
“…In the search for more objective prognostic factors for adequate returns to work, biological parameters have been evaluated [ 6 ]. Our previous study [ 7 ] examined the usefulness of autonomic measurement in predicting the outcome of a return to work. In that study, heart rate variability (HRV) was used to evaluate autonomic activity at the time of reinstatement, and significant differences were observed between the HRV data of the depressed patients who returned to work successfully and those who did not.…”
Section: Introductionmentioning
confidence: 99%
“…Our study reported that these abnormal HRV profiles continue to be present at the time of return in patients whose return is unsuccessful despite their depressive symptoms having lessened [ 7 ]. The results suggest that abnormal HRV is related to a residual depressive state and can be linked to a patient’s lack of ability to perform work, as autonomic controllability is important in occupational activities and in the ability to face stressful events at work.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations